Clinical and economic outcomes of nurse-led services in the ambulatory care setting: A systematic review. (May 2018) - Chan, Raymond J.; Marx, Wolfgang; Bradford, Natalie; Gordon, Louisa; Bonner, Ann; Douglas, Clint; Schmalkuche, Diana; Yates, Patsy
Abstract: Background: With the increasing burden of chronic and age-related diseases, and the rapidly increasing number of patients receiving ambulatory or outpatient-based care, nurse-led services have been suggested as one solution to manage increasing demand on the health system as they aim to reduce waiting times, resources, and costs while maintaining patient safety and enhancing satisfaction. Objectives: The aims of this review were to assess the clinical effectiveness, economic outcomes and key implementation characteristics of nurse-led services in the ambulatory care setting. Design: A systematic review was conducted using the standard Cochrane Collaboration methodology and was prepared in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Data sources: We searched the Cochrane Central Register of Controlled Trials (CENTRAL) on The Cochrane Library, MEDLINE EBSCO, CINAHL EBSCO, and PsycINFO Ovid (from inception to April 2016). Review methods: Data were extracted and appraisal undertaken. We included randomised controlled trials; quasi-randomised controlled trials; controlled and non-controlled before-and-after studies that compared the effects of nurse-led services in the ambulatory or community care setting with an alternative model of care or standard care. Results: Twenty-five studies of 180, 308 participants were included in this review. Of the 16 studies that measured and reported on health-related quality of life outcomes, the majority of studies (n = 13) reported equivocal outcomes; with three studies demonstrating superior outcomes and one demonstrating inferior outcomes in comparison with physician-led and standard care. Nurse-led care demonstrated either equivalent or better outcomes for a number of outcomes including symptom burden, self-management and behavioural outcomes, disease-specific indicators, satisfaction and perception of quality of life, and health service use. Benefits of nurse-led services remain inconclusive in terms of economic outcomes. Conclusions: Nurse-led care is a safe and feasible model of care for consideration across a number of ambulatory care settings. With appropriate training and support provided, nurse-led care is able to produce at least equivocal outcomes or at times better outcomes in terms of health-related quality of life compared to physician-led care or standard care for managing chronic conditions. There is a lack of high quality economic evaluations for nurse-led services, which is essential for guiding the decision making of health policy makers. Key factors such as education and qualification of the nurse; self-management support; resources available for the nurse; prescribing capabilities; and evaluation using appropriate outcome should be carefully considered for future planning of nurse-led services.